Postpartum sterilization: a five years retrospective study - Dhanapal, Mohana; Sivanandan, Kotteeswari Palanisamy; Sengottian, Eswari; Murugesan, Praveena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Female sterilization, which is also called tubal ligation or tubal occlusion, is a surgical procedure which aims at permanent contraception. When female sterilization is performed at the time of birth with caesarean delivery or very soon after vaginal birth, such sterilization is called puerperal or postpartum sterilization. This study is to analyse the puerperal sterilization done in our hospital regarding age, living children, timing of sterilization and complications. Methods: A retrospective analytical study of 6069 cases of puerperal sterilization performed over a period of 5 years from January 2013 to December 2017. Results: During the study period, 6069 cases of puerperal sterilization cases were done. Out of which 4714 (77.67%) patients had undergone caesarean tubectomy, 1355 (22.32%) patients had undergone mini-laparotomy. Maximum number of patients was in the age group of 20-29yrs (80.3%). Majority of patients (68.62%) had two living children. Complications were encountered in 32.38% of patients. Conclusions: The findings in this study showed that the incidence of voluntary surgical contraception is low. Adequate education and counseling will lead to acceptance of the procedure and consequently, a reduction in high maternal mortality from unwanted pregnancies.